MORPHOLOGICAL END IMMUNOHISTOCHEMICAL FEATURES PLACENTAS OF WOMEN WITH INFERTILITY AFTER ART - Бойчук, О.Г.; Бойчук-Товcта О.Г. (World of Medicine and Biology, 2018)
In women with endocrine infertility after form of assisted reproductive technologies, an increase in weight of the placenta. In 50% of placentas marked focus relative immaturity of the type of dissociated katyledoniv, violation of blood circulation against the background of compensatory reactions of moderate severity. Morphometric observed dominance of villous capillaries single, centrally located, leading to a significant reduction in the number syntsytiokapilyarnyh membranes and reduces the number of special terminal villi and permeability in violation of the placenta. Significantly increasing the number of fruit and mizhvorsynchatoho fibrynoyidu glued fibrynoyidom villi, syncytial knots, heart attacks, reduced mizhvorsynchastyy and vascular space, there is a thinning of the epithelium villi, increased compensatory anhiomatoz vessels. These changes reflect poor circulation and permeability of the placenta, impair its functional capability and is the pathological background against which developing obstetric and perinatal disorders. The absence or downregulation of e-NOS as the most functionally important structures, the majority (60%) placentas of women with long-term hormonal support during pregnancy induced demonstrates the lack of compensatory responses, endothelial dysfunction, disturbance of macro- and microcirculation, and as a result - a reduction of functionality placenta.